ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS TULUNGAGUNG - Eko Santoso; Latifatul Isro'iyah; Andrean Kresna Wahyudiantoro (BEMJ : Business, Entrepreneurship, and Management Journal, 2023)
It is common knowledge that education is linked to unemployment, particularly among educated workers, despite expectations that good education can provide human resources of high quality. Entrepreneurship education is one of the factors that has a substantial impact on students' entrepreneurial interest, according to Lestari and Wijaya (2012). In order to determine how much the factors that influence entrepreneurial interest in students at the Faculty of Economics at Tulungagung University influence that interest, the author will conduct this research using quantitative research methods. The population of this study consists of 74 students from the Tulungagung University's Faculty of Economics, including 40 males and 34 women. According to the author's research findings, income expectations, family environment, and entrepreneurship education do not interact. Students at Tulungagung University's Faculty of Economics have an increased interest in entrepreneurship as a result of receiving entrepreneurial education. The family environment has a favorable impact on the entrepreneurial interest of students at Tulungagung University's Faculty of Economics. Income expectations have no favorable impact on Tulungagung University's Faculty of Economics students' motivation in starting their own business. Keywords: entrepreneurship, entrepreneurship education, income expectation